Trade development between China and countries along the Belt and Road: A spatial econometric analysis based on trade competitiveness and complementarity. (28th June 2020) - Chen, Jiyong; Chen, Dabo; Yao, Aiping
Abstract: This paper empirically analyses the effect of trade competitiveness and complementarity on the trade development between China and the countries along the Belt and Road (B&R). The study first measures the trade competitiveness and the complementarity between China and the countries along the B&R by using the trade competitiveness coefficient ( TCC ) and the trade complementarity index ( TCI ). Then a spatial gravity model is constructed to analyse the effect of trade competitiveness and complementarity on trade development between China and the countries along the B&R. We use generalized method of moments (GMM) and spatial filtering technology to verify the robustness of the model. The results show that the GDP of China and the countries along the B&R, the land area of countries along the B&R, trade complementarity, common language, free trade agreements (FTA), and the B&R Initiative significantly promote the trade development between China and the countries along the B&R, whereas the geographical distance between countries and trade competitiveness significantly inhibit it. Finally, to promote the trade development between China and the countries along the B&R, the present paper puts forward suggestions including improving trade promotion policies between China and the countries along the B&R and vigorously expanding cooperation with complementary industries in the countries along the B&R to enhance trade dependence.